Potential distribution of Abies vejarii (Pinaceae) and its relationship with environmental, topographic and anthropogenic factors in northeastern Mexico - González-Cubas, Rigoberto; Treviño-Garza, Eduardo Javier; Aguirre-Calderón, Oscar Alberto; Foroughbakhch-Pournavab, Rahim (Instituto de Ecología, A.C., 2020)
Background and Aims: Abies vejarii (oyamel) is an endemic species of northeastern Mexico, currently listed as Near Threatened by the InternationalUnion for the Conservation of Nature (IUCN), with isolated populations. The objectives of the present study were i) to look for areas where the idealconditions for oyamel development meet, using the maximum entropy algorithm in the Sierra Madre Oriental (SMOR), ii) identify the topographic environmental variables associated with its current distribution, and iii) evaluate the current anthropogenic impacts on the distribution of A. vejarii.Methods: Using a species distribution model (MDE), the suitability of its habitat was modeled, with bioclimatic and topographic data. The environmental variables that influence its geographical distribution were identified through cluster (CA) and principal component analyses (PCA). Finally, the effect of the anthropogenic impact was linked with its current distribution areas.Key results: The total area that is predicted and that is climatically adequate for its presence was 67,096 ha. The analysis of the environmental and topographic variables showed that the annual temperature range and the precipitation of the driest month were the most important. A negative and significant association with the anthropogenic impact was found. The Sierra Madre Oriental presents the conditions that are the favorable habitat for the persistence of A. vejarii.Conclusions: The quantification of the optimal areas that allow the establishment and development of A. vejarii will make it possible to design strategies and prescribe actions for the conservation and restoration of populations of this species.